The Effectiveness of the Implementation of Learning Supervision in Improving the Quality of Learning - Arina, Yudela; Yolanda, Septiara; Revita, Yuni; Marsidin, Sufyarma; Rifma, Rifma (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
The phenomenon related to this research is that until now, the learning media used by teachers is still very minimal. It can be seen from the broken focus that the internet network still needs improvement, and the time used to carry out supervision could be a lot higher because the principal has the task. For the most part, this is one of the inhibiting factors in the process of supervised learning in this school and will also affect the quality of learning, impacting student learning outcomes. This type of field research uses qualitative research methods or approaches. This study used the principal and several teachers who taught as respondents or resource persons. This study concludes that the implementation of learning supervision has been effective because learning supervision can be a benefit that directs, encourages, spurs, and surveys instructors in the utilization of learning. The strategy applied by the teacher to improve the quality of learning is that the teaching and learning process must start with planning learning activities, learning methods, media used, face-to-face, and class management, then observed and evaluated. The principle in providing services to teachers so that the learning process can run smoothly is good, where the principal assists teachers in planning, implementing, and assessing learning program activities and assisting teachers in preparing teaching and learning activities.